2013
DOI: 10.1093/mnras/stt1581
|View full text |Cite
|
Sign up to set email alerts
|

Substructure and dynamical state of 2092 rich clusters of galaxies derived from photometric data

Abstract: Dynamical state of galaxy clusters is closely related to their observational properties in X-ray, optical and radio wavelengths. We develop a method to diagnose the substructure and dynamical state of galaxy clusters by using photometric data of Sloan Digital Sky Survey (SDSS). To trace mass distribution, the brightness distribution of member galaxies is smoothed by using a Gaussian kernel with a weight of their optical luminosities. After deriving the asymmetry, the ridge flatness and the normalized deviation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
109
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 142 publications
5
109
0
2
Order By: Relevance
“…Sommer & Basu (2014) constructed near-complete samples based on X-ray and SZ catalogs. They found that roughly 70%±10% of the clusters in the X-ray selection have no radio halos (indicating they are relaxed), whereas the fraction in the Planck selection is only 30±10%, in agreement with findings from Wen & Han (2013) and McDonald et al (2013).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Sommer & Basu (2014) constructed near-complete samples based on X-ray and SZ catalogs. They found that roughly 70%±10% of the clusters in the X-ray selection have no radio halos (indicating they are relaxed), whereas the fraction in the Planck selection is only 30±10%, in agreement with findings from Wen & Han (2013) and McDonald et al (2013).…”
Section: Introductionsupporting
confidence: 73%
“…Planck Collaboration et al (2011Collaboration et al ( , 2013 presented the first observational evidence of different morphological properties in X-ray-selected versus SZ-selected samples: SZ-selected clusters have a less peaked density distribution and are less X-rayluminous at a given mass than X-ray-selected clusters. Wen & Han (2013) presented a method to diagnose the substructure and dynamical states for 2092 optical galaxy clusters. They found that the fraction of relaxed clusters is 28% in the full sample, while the fraction increases to 46% for the subsample matched with ROSAT detections, indicating that the wavelength used for detecting clusters plays a significant role in the dynamical state of the population that is selected.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in a very recent work, Wen & Han (2015) have analyzed the dependence of the bright end of the LF on the cluster dynamical state. They used the method presented in Wen & Han (2013) to create three subsamples of clusters with different dynamical states. They conclude that more relaxed clusters have fainter M * .…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…At the same time, the advent of multi-band photometric data has led to dramatic improvements in optical cluster finding and an explosion of algorithms (e.g. Gladders & Yee 2005;Koester et al 2007;Wen & Han 2013;Hao et al 2010;Szabo et al 2011, and many others).…”
Section: Introductionmentioning
confidence: 99%